Study of the Impact of Past Extreme Solar Events on the Modern Air Traffic - G. Hubert; S. Aubry (Space Weather)
Abstract The ancient solar energetic particle (SEP) events of 774/775 CE and 993/994 CE were characterized thanks to radionuclide productions stored in environmental archives as ice cores or tree rings. Primary cosmic ray spectra deduced from these cosmogenic isotope data indicate that the impact of these extreme SEP events would have been much more significant than any of the ones observed during the modern era. However, the impact of these should be studied more accurately in the framework of the ambient dose equivalent impacting aircrew and passengers in the air traffic context by considering physical parameters such as time profile or anisotropy properties. In this study, the impact that 774/775 CE and 993/994 CE past extreme SEP events could have had on modern air traffic is discussed. Possible event spectra for these ancient events are derived from the spectra ground‐level enhancement (GLE) 5 and GLE 69, which have been observed during the modern era and have been widely studied/characterized using measurements. The investigations include the impact of the SEP activity on ambient dose equivalent, including detailed analyses considering route, airplane characteristics (departure, arrival, continent, airplane type), and the time occurrence of the SEP event. Statistical analyses show that additional dose levels can reach values on the order of 70 mSv, which is absolutely significant considering the current air traffic recommendations. The orders of magnitude of the ambient dose equivalent induced during past extreme SEP events raises a number of issues, both for aircrews and for avionics hardware. This study demonstrates that simulations can be useful for the evaluation of risks in case of extreme SEP events.